RANCANG BANGUN SISTEM INFORMASI DESA BERBASIS WEBSITE PADA DESA KEDUNGJAYA KECAMATAN BABELAN KABUPATEN BEKASI - Guido Arya Satya, (2023)
Kedungjaya Village is a village that has not utilized information technology. The lack of village-related information, poor village information dissemination, and village data collection, such as population data, are still using a manual system. This problem causes information in the village to be less well publicized, so that the village community and people outside the village have minimal information regarding Kedungjaya village itself. In addition, village data collection is still manual, resulting in ineffective and efficient data collection. This data is difficult to manage by Kedungjaya village officials. The purpose of this research is to design a Website-based village information system that can assist the Kedungjaya village administration in collecting population data and disseminating village information so that the Kedungjaya village community can obtain fast and accurate information and village officials can manage village data easily. The method used to support research is Scrum, so that an application that is as expected can be produced. The results of this study are a Website-based village information system that can provide village information to the community and facilitate village administration in collecting data on Kedungjaya village.